2021
DOI: 10.1038/s41405-021-00090-5
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiling on effect of aspirin on osteogenic differentiation of periodontal ligament stem cells

Abstract: Periodontal ligament (PDL) contains a unique population of mesenchymal stem cells (MSCs), also known as PDL stem cells (PDLSCs). The regenerative properties of PDLSCs hold great potential for its use in stem cells based therapy, particularly for periodontal or bone regeneration. The present study investigated the global gene expression profile in PDLSCs during osteogenic differentiation. MSCs from PDL were isolated from normal permanent human teeth (n = 3). Microarray analysis was used to study the effects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…There were just four papers published reporting the results of ex vivo studies. 15,16,17,18 These outline early pre-clinical studies of new health technologies (new materials, methods and pharmacological interventions) and in vitro studies of existing technologies. These were relatively more frequent in the early days of BDJ Open, but this journal now covers the whole range of dental research.…”
Section: Pre-clinical/ex Vivomentioning
confidence: 99%
“…There were just four papers published reporting the results of ex vivo studies. 15,16,17,18 These outline early pre-clinical studies of new health technologies (new materials, methods and pharmacological interventions) and in vitro studies of existing technologies. These were relatively more frequent in the early days of BDJ Open, but this journal now covers the whole range of dental research.…”
Section: Pre-clinical/ex Vivomentioning
confidence: 99%
“…For instance, lncRNA H19 promotes osteoblast differentiation via the TGF-β1/SMAD3/HDAC pathway by encoding miR-675 (Huang et al, 2015), while lncRNA MALAT1 enhances osteoblast differentiation through SMAD4 up-regulation by sequestering miR-204 (Xiao et al, 2017). Numerous studies have independently investigated both human coding and lncRNA gene expression profiles during osteogenic differentiation (Abd Rahman, 2021; Håkelien et al, 2014; Hong et al, 2020; Huang et al, 2017; Khodabandehloo et al, 2020; Liu et al, 2020; Park et al, 2015; Qiu et al, 2017; Shaik et al, 2019; Skårn et al, 2014; Song et al, 2015; Sun et al, 2019; Twine et al, 2014; Wang et al, 2015; Xia et al, 2020; Zhang et al, 2017; Zheng et al, 2018). However, many of these studies are limited by such factors as reliance on microarrays, small sample sizes, and brief osteogenic differentiation periods.…”
Section: Introductionmentioning
confidence: 99%
“…8 Recent studies reported that Aspirin is capable of stimulating the various dental stem cells, this promotes the migration, proliferation, and differentiation of odontoblast cells responsible for the enhance the regeneration of dentin. [9][10][11] These findings strongly suggest that Aspirin has excellent potential in the management of several dental problems for which there is no clear-cut treatment strategy. Hence, Aspirin's therapeutic effectiveness depends on the design and development of a suitable novel drug delivery system for Aspirin.…”
Section: Introductionmentioning
confidence: 99%